A crossover in the temperature behavior of the perpendicular upper critical magnetic field of layered superconductors and thin films - Gvozdikov, V.M. (Физика низких температур, 1999)
A mechanism which relates the upturn of the perpendicular upper critical magnetic field H┴с₂ (T) in layered superconductors and thin films with the structural inhomogeneity in the bulk of the sample, provided that the local critical temperature Tc* inside the inhomogeneity is higher than in the rest of the sample (Tc) is proposed. Within the Ginzburg-Landau approach an equation whic h describes two types of experimentally observed nonlinearities in H┴с₂ (T) near Tc for ISN (insulator-superconductor-normal metal) and NSN layer configurations, is found. In the NSN case a crossover from the linear branch H┴с₂ (T) ⋉ (Tc-T), for fields H ≤ Hₘ, to the nonlinear branch with the upturn, if H > Hₘ, takes place. The crossover field Hₘ is inversely proportional to the local enhancement of the critical temperature (Tc*-Tc) and the distance R to the surface (the nearest surface, in case of a thin film). In the ISN case the upturn holds for H<Hₘ, whereas for higher fields H┴с₂ (T) crosses over to the linear branch. In the ISI case the H┴с₂ (T) is a linear function.